Nocturnal hypoxemia is associated with poor pulmonary hemodynamics in patients with chronic thromboembolic pulmonary disease - Teng Han; Qiang Huang; Zhenguo Zhai; Xiaolei Zhang (Respiratory Research)
Abstract Background Although a general association between nocturnal hypoxemia or sleep-disordered breathing (SDB) and pulmonary arterial hypertension has been established, little is known about the unique pathophysiologic contributions of SDB and nocturnal hypoxemia to chronic thromboembolic pulmonary disease (CTEPD). We therefore chose to examine the associations of SDB and nocturnal hypoxemia with hemodynamic indices obtained via right heart catheterization (RHC) in hospitalized patients with CTEPD. We hypothesized that the severity of CTEPD would be associated with SDB and nocturnal hypoxemia severity. Methods Patients with CTEPD with or without pulmonary hypertension (PH) who had undergone polysomnography (PSG) between July 2022 and March 2024 were enrolled. A nocturnal mean oxygen saturation by pulse oximetry (MeanSpO2) < 90% was defined as nocturnal hypoxemia, and a percentage of total sleep time with oxygen saturation < 90% (T90) exceeding 20% indicated severe nocturnal hypoxemia. The relationships between right heart catheterization measurements and T90 or MeanSpO2 were calculated using multiple linear regression and logistic regression analyses. Results The prevalence of severe nocturnal hypoxemia in the entire cohort was 42.86%, and SDB (AHI ≥ 15/h) affected 55.84% of patients and was predominantly manifested as hypopnea. Nocturnal hypoxemia remained significantly associated with mean pulmonary artery pressure (mPAP) (T90: β = 0.296, P = 0.019; MeanSpO2: β= -0.333, P = 0.009) and pulmonary vascular resistance (PVR) (T90: β = 0.294, P = 0.021; MeanSpO2: β=-0.310, P = 0.015) after adjusting for age, sex, body mass index, apnea hypopnea index and diurnal arterial partial pressure of oxygen. Receiver operating characteristic (ROC) curves for the detection of a mPAP ≥ 25 mmHg, PVR > 3 WU and WHO FC III-IV indicated that nocturnal hypoxemia parameters had moderate predictive value. (T90: AUCmPAP=0.698, AUCPVR=0.733, AUCWHO−FC=0.729, respectively; MeanSpO2: AUCmPAP=0.691, AUCPVR=0.731, AUCWHO−FC=0.707, respectively). Conclusions SDB is highly prevalent in patients with CTEPD, which is predominantly manifested as hypopnea rather than apnea, and overweight is not a commonly reported characteristic. Independent of the severity of SDB, nocturnal hypoxemia is significantly correlated with hemodynamics in patients with CTEPD, which indicated the clinical necessity of promoting nocturnal oximetry monitoring among patients with CTEPD.